1993
DOI: 10.1111/j.1432-1033.1993.tb18369.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lysine ionization on the structure and electrochemical behaviour of the Met44→Lys mutant of the blue‐copper protein azurin from Pseudomonas aeruginosa

Abstract: The structural and spectrochemical effects of the replacement of Met44 in the hydrophobic surface patch of azurin from Pseudomonas aeruginosa by a lysine residue were studied as a function of the ionization state of the lysine. In the pH range 5 -8, the optical absorption, resonance Raman, EPR and electron spin-echo envelope modulation spectroscopic properties of wild-type and Met44-+Lys (M44K) azurin are very similar, indicating that the Cu-site geometry has been maintained. At higher pH, the deprotonation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…Most likely the different pH dependencies of Tt-Cu A and Cu A -Azu can be partially ascribed to the protonable His35 residue in Cu A -Azu, which is very close to the active site. 21,22 Our results highlight the importance of the protein matrix acting as a second (and higher) coordination sphere in regulating both the electronic and redox properties of the Cu A redox centre, which is consistent with the differential role of the weak axial ligand methionine in regulating thermodynamic and kinetic ET parameters, as reported recently. 8,14 Moreover, they challenge the notion of redox properties of the primary electron acceptor of CcO being fine-tuned by local variations of pH in vivo.…”
supporting
confidence: 90%
“…Most likely the different pH dependencies of Tt-Cu A and Cu A -Azu can be partially ascribed to the protonable His35 residue in Cu A -Azu, which is very close to the active site. 21,22 Our results highlight the importance of the protein matrix acting as a second (and higher) coordination sphere in regulating both the electronic and redox properties of the Cu A redox centre, which is consistent with the differential role of the weak axial ligand methionine in regulating thermodynamic and kinetic ET parameters, as reported recently. 8,14 Moreover, they challenge the notion of redox properties of the primary electron acceptor of CcO being fine-tuned by local variations of pH in vivo.…”
supporting
confidence: 90%
“…The bimolecular electron transfer rate of B 10 4 M − 1 s − 1 between the two molecules of S118C azurin dimer is also slow, as compared with wild type azurin ( 10 6 M − 1 s − 1 ). The hydrophobic patch surrounding His117 has been shown to be the site of interaction for intermolecular electron transfer [1][2][3][4]. As a result of the dimerization this patch is expected to be no longer exposed to the solvent and, thus, to have become inaccessible for other dimers to form association complexes.…”
Section: Electron Self Exchange Ratesmentioning
confidence: 99%
“…Although the structure of the binary complex in the e.s.e. reaction is unknown, NMR studies have shown that the hydrophobic patch surrounding the surface exposed copper ligand His117 is the site of interaction [1][2][3][4]. A clear demonstration of how the association of two molecules along this patch may occur, is provided by the crystal structure, where two water molecules connect the two His117 copper ligands via hydrogen bonds [5,6].…”
Section: Introductionmentioning
confidence: 99%